Cultivation systems, corn variety and Azospirillum - alternatives for small rural properties - de Oliveira Xavier, Letícia; Roberto Valicheski, Romano; Rodrigues de Carvalho, Eduardo; Martins Oliveira, Lorena; de Sousa Peres, Mateus; Lafaete Freitas Lourenço , Jhonatan; Moreira Alves, Estenio; Lopes Claudio, Flavio (Seven Editora, 2023)
In the Western region of Goiás, the agricultural activity carried out by small producers predominates, many of which are dissatisfied with the production of corn for silage, due to its high production cost. Thus, it was evaluated the response of genetic materials of corn (variety SCS 154, SCS 156e hybrid Dow 2A620PW), grown in a solitary way and intercropped with pumpkin, with and without Azospirillum brasilense as inoculant for phytotechnical and productive aspects, seeking viable alternatives for family agriculture.   The experiment was carried out in strips, sowing 1 hectare of corn and 1 hectare of pumpkin in monoculture; and, 1 hectare of corn + pumpkin in consortium.  The sowing was performedon 11/15/2018, being for mechanized corn, and for pumpkin, manually.  For pumpkin, higher productivity (13.11 t.ha-1) was obtained in the single system. For corn, there was no influence of cultivation systems on grain yield.  The use of Azospirillum was efficient, providing better development in corn plants, however, there was a differentiated response of the genéticmaterials to the inoculant. The hybrid showed higher grain yield (5,536 kg.ha-1),, while the tested  varieties showed higher dry mass production by shoots, making it promising  in the production of bulky foods.